2019
DOI: 10.3808/jei.201800402
|View full text |Cite
|
Sign up to set email alerts
|

DCT-based Least-Squares Predictive Model for Hourly AQI Fluctuation Forecasting

Abstract: Recently the issue of air quality has become a global public health concern. As air pollution has been reported as the largest single environmental health risk in the world, analysis and prediction of air quality is increasingly important. Norm ally, either statistical models or CTM ("deterministic chemistry-transport") models are used for forecasting air PM ("particulate matter") levels. Actually, hourly air quality fluctuation is also one time-series. Compared with commonly used deterministic photochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The outputs (https://esgf-node.llnl.gov/search/cmip5/) from five GCMs (i.e., IPSL‐CM5A‐LR, MIROC5, GFDL‐ESM2M, CSIRO‐Mk3.6.0, and CNRM‐CM5) are downloaded from the Coupled Modeling Intercomparison Project (CMIP5) data set archive. These five models are commonly employed in previous studies (Li et al., 2016; Yang, 2020). More details about these five GCMs can be found in Table S1.…”
Section: Methodology and Data Collectionmentioning
confidence: 99%
“…The outputs (https://esgf-node.llnl.gov/search/cmip5/) from five GCMs (i.e., IPSL‐CM5A‐LR, MIROC5, GFDL‐ESM2M, CSIRO‐Mk3.6.0, and CNRM‐CM5) are downloaded from the Coupled Modeling Intercomparison Project (CMIP5) data set archive. These five models are commonly employed in previous studies (Li et al., 2016; Yang, 2020). More details about these five GCMs can be found in Table S1.…”
Section: Methodology and Data Collectionmentioning
confidence: 99%
“…It was observed that selecting appropriate parameters was the key to the study and improved the capability of the PSO algorithm. The improvement equation was Equation (7).…”
Section: Ipsomentioning
confidence: 99%
“…The classic time series analysis is a standard statistical technique. The autoregressive, moving average, autoregressive moving average, and autoregressive integrated moving average (ARIMA) models are classical statistical models used in this field [7]. TRIPTI et al [8] used the seasonal ARIMA (SARIMA) model and forecast future trends by making the data stationary.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the application of the LS method is widespread in climate data analysis, including wind energy data [23,24] and air humidity data [25]. Utilizing LS in forecasting hourly fluctuations in the Air Quality Index (AQI) achieved an accuracy level of 93.24%, signifying a remarkably high precision [26]. In their study on monthly temperature estimation using the Partial Least Square (PLS) method, Ertaç et al [27] reported an RMSE value of 1.80% and a high accuracy level of 94%.…”
Section: Introductionmentioning
confidence: 99%